Menghitung Tinggi Matahari dan Mengukur Azimut Matahari - Ramadini, Tan Dwi Rizki (Jurnal Pelita Nusantara, 2025)
The position of the Sun in the sky plays an important role in various fields such as astronomy, navigation, and timekeeping. This position can be determined through the measurement of the Sun’s altitude and azimuth, which are part of the horizontal coordinate system in astronomy. This study aims to determine the Sun’s altitude and azimuth at a specific time using the shadow of a vertical stick (gnomon). The observation was conducted using a direct observation method on April 6, 2025, at 13:01 WIB in Kampung Angus, Tanjung Bugis Village, Sambas. The gnomon used was 20 cm high, and its shadow measured 7.9 cm in the eastward direction. Based on this data, trigonometric calculations were performed to obtain the Sun’s altitude of 68.45° and an azimuth of 270° indicating that the Sun was positioned precisely to the west at the time of observation.